2022
DOI: 10.1371/journal.pone.0260855
|View full text |Cite
|
Sign up to set email alerts
|

A novel autotransfusion device saving erythrocytes and platelets used in a 72 h survival swine model of surgically induced controlled blood loss

Abstract: Background The purpose of this study was to develop a swine model of surgically induced blood loss to evaluate the performances of a new autotransfusion system allowing red blood cells and platelets preservation while collecting, washing and concentrating hemorrhagic blood intraoperatively. Methods Two types of surgically induced blood loss were used in 12 minipigs to assess system performance and potential animal complications following autotransfusion: a cardiac model (cardiopulmonary bypass) and a viscera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…The blood processing by the device has been extensively described in published preclinical reports. 16,17 Briefly, shed blood is collected and heparinized through a dual-lumen suction line in a sterile blood collection reservoir (including a 40-μm filter) previously primed with 200 ml of the heparinized 0.9% NaCl solution (heparinized saline drip 25,000 U/l). The salvaged blood is then treated by the device with both filtration and washing with 0.9% NaCl solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood processing by the device has been extensively described in published preclinical reports. 16,17 Briefly, shed blood is collected and heparinized through a dual-lumen suction line in a sterile blood collection reservoir (including a 40-μm filter) previously primed with 200 ml of the heparinized 0.9% NaCl solution (heparinized saline drip 25,000 U/l). The salvaged blood is then treated by the device with both filtration and washing with 0.9% NaCl solution.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies recently demonstrated a high performance in both red blood cell recovery and plasma proteins and heparin washing. 16,17 Further, the i-SEP device achieved a significant platelet recovery with minimal platelet activation while maintaining platelet ability to be activated in vitro. 16 Our objective was to evaluate in a first-in-human study the cell recovery performance and the biologic safety of the i-SEP device during on-pump cardiac surgery.…”
mentioning
confidence: 97%